2020
DOI: 10.3390/jcm9082502
|View full text |Cite
|
Sign up to set email alerts
|

Survival in Patients with Neuroendocrine Tumours of the Small Intestine: Nomogram Validation and Predictors of Survival

Abstract: Neuroendocrine tumours of the small intestine (SI-NETs) are rare and heterogeneous. There is an unmet need for prognostication of disease course and to aid treatment strategies. A previously developed nomogram based on clinical and tumour characteristics aims to predict disease-specific survival (DSS) in patients with a SI-NET. We aimed to validate the nomogram and identify predictors of survival. Four hundred patients with a grade 1 or 2 SI-NET were included, between January 2000 and June 2016. Predicted 5- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 53 publications
0
16
0
3
Order By: Relevance
“…The nomogram rose in response to the proper time and conditions based on these systems, including effective variables to enhance predictive ability. Regarding the nomogram in NENs, preceding studies have demonstrated its predictive value in the OS of gastric neuroendocrine neoplasms ( 26 ), the pancreas ( 27 , 28 ), the small intestine ( 29 , 30 ), the rectum ( 31 ), and the digestive system ( 32 ). These outcomes all signal that a specific, clinically applicable nomogram can accurately estimate the prognosis of patients with NENs.…”
Section: Discussionmentioning
confidence: 99%
“…The nomogram rose in response to the proper time and conditions based on these systems, including effective variables to enhance predictive ability. Regarding the nomogram in NENs, preceding studies have demonstrated its predictive value in the OS of gastric neuroendocrine neoplasms ( 26 ), the pancreas ( 27 , 28 ), the small intestine ( 29 , 30 ), the rectum ( 31 ), and the digestive system ( 32 ). These outcomes all signal that a specific, clinically applicable nomogram can accurately estimate the prognosis of patients with NENs.…”
Section: Discussionmentioning
confidence: 99%
“…After a careful revision of the small bowel diseases small bowel diseases excised tumor with the loco-regional lymph nodes, the patient underwent an enlargement of the surgical margin and lymphadenectomy. NETs were considered rare; however, with the advancement and availability of new diagnostic modalities such as the endoscopic capsule, an increasing number of this neoplasia has been diagnosed (Ahmed, 2020;Deguelte et al, 2020;Folkestad et al, 2020;Levy et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…More useful diagnostic resources include determination of CgA, SYP, neuron-specific enolase (NSE), and 5-hydroxy indole acetic acid (in cases of carcinoid syndrome); CE and balloon-assisted or spiral endoscopy; and imaging study as SRS (Octreoscan), Ga-DOTATATE PET/CT or 111In-TPA-Octreotide scan (Ahmed, 2020;Deguelte et al, 2020;Levy et al, 2020;Pérez-Cuadrado-Robles et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations